Effect of annealing temperature on morphological, structural and optical properties of nanostructured CuO thin film - Akgul, Unal; Yildiz, Koksal; Atici, Yusuf (Springer Heidelberg, 2016)
CuO thin film was grown on a glass substrate by reactive radio frequency (rf) magnetron sputtering. The deposited film was annealed in air at various temperatures for 2 h. The SEM images showed that the grain size increased with rising annealing temperature. The EDX and XRD results revealed that the chemical composition and phase of the polycrystalline film were not affected by the annealing conditions. The optical band gap increased from 2.244 eV to 2.261 eV and then decreased from 2.261 eV to 2.145 eV by the effect of annealing temperature.
Keywords: Physical-Properties; Substrate; Growth; Cell